Calcareous plankon bio-events in the Miocene Case Pelacani section (Sicily, Italy) - DI STEFANO, E.; BONOMO, S.; CARUSO, A.; DINARÉS-TURELL, J.; FORESI, L. M.; SALVATORINI, G.; SPROVIERI, R. (2002)
The upper Serravallian-lower Tortonian Case Pelacani section in Sicily is composed of the epipelagic sediments of the Tellaro Formation. The section, made of four easily correlated segments, records a more or less continuous sequence of lithologic couplets, with whitish marls and blackish levels in the lower part and whitish marls and whitish, more indurate levels in the upper part. The distribution of the most common taxa of planktonic foraminifera and calcareous nannofossils was estimated quantitatively in 316 samples, collected every 20 cm along the section which is 66.35 in thick. Eleven planktonic foraminifera (only the eight marker events were estimated quantitatively) and five calcareous nannofossil bio-events were identified. Their astrochronology was extrapolated by correlating them with the cyclostratigraphic results obtained for this section, and published separately. The ages compare well with the ages published for the same events in other Mediterranean sections. Paleomagnetic analysis along 30 meters in the central part of the section gave puzzling results and therefore no reliable magnetostratigraphy could be obtained. The Case Pelacani section, straddling the stratigraphic interval which starts slightly below the first occurrence and ends slightly above the first regular occurrence of Neogloboquadrina acostaensis, is a good candidate for the definition of the GSSP (Global Stratigraphic Section and Point) of the Tortonian. Independently from the section selected, we suggest to define the Serravallian/Tortonian boundary in a level coincident with or near the last occurrence of Paragloborotalia siakensis, as previously proposed, or coincident with or near the last common occurrence (LCO) of Globigerinoides subquadratus. This latter level virtually coincides with the first common occurrence (FCO) of Globigerinoides obliquus obliquus and is slightly above the last regular occurrence (FRO) of Discoaster kugleri, which occurs only 2.25 meters (and 3 precessional cycles) below in the section under study.